Use Of First Loan Applications on A Fellow Contact Basis (Case Study: FEB UMY Student) - Pajar, Eval; Nida, Fathiya Zhahira; Wiranatakusuma, Dimas Bagus (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Online lending refers to the process of applying for a loan through a digital platform or app that allows individuals or businesses to obtain borrowed funds quickly and easily. Online lending usually has a simpler and faster application process compared to traditional financial institutions such as banks. This study aims to explore the utilization of peer-to-peer lending applications in the context of online lending. The app allows users to borrow funds quickly and easily from their contacts within the app. This research will involve collecting qualitative data through preferences from FEB UMY students. The pinlu application is expected to be a solution for students of the Faculty of Economics and Business, Universitas Muhammadiyah Yogyakarta.